Condensation and expansion characteristics of water steam and carbon dioxide in a Laval nozzle. (15th May 2019) - Deng, Qinghua; Jiang, Yu; Hu, Zhifeng; Li, Jun; Feng, Zhenping
Abstract: The condensation of water steam in Rankine cycle's turbines occurs usually at the subcritical region far away from the critical point, while that of the supercritical carbon dioxide in Brayton cycle' compressors occurs generally at the supercritical region and near the critical point. However, it's not known about that flow characteristics of those common, condensable working fluids in the range of subcritical and supercritical regions. In this paper, the equilibrium condensation and expansion characteristics of water steam and CO2 in a Laval nozzle under the same dimensionless nozzle inlet conditions were investigated numerically. Firstly, the results show that the wetness fraction distribution of each working fluid is different under different nozzle inlet conditions, while the variation trend of wetness fraction are totally similar for both working fluids. This phenomenon implies that the main factor that influences the variation trend of wetness fraction is the nozzle inlet conditions rather than the type of working fluids. Secondly, the nozzle outlet Mach number of CO2 is lower than that of water steam. And with the increasing of inlet total pressure, the total pressure loss decreases, and that of CO2 is lower than that of water steam under the same nozzle inlet conditions. Highlights: Condensation characteristics of H2 O and CO2 in all ranges are compared. Affecting factor of condensation is nozzle inlet conditions rather than fluids. Condensation at supercritical region should be paid much more attention. Total pressure loss decreases with the increasing of nozzle inlet total pressure. Total pressure loss of CO2 is lower than that of H2 O under same inlet conditions.